The Effect of Particle Size on the Mechanical Properties of Alkali Activated Steel Slag Mortar - Doh, Shu Ing; Chia, Min Ho; Li, Xiaofeng; Putra Jaya, Ramadhansyah; Mohd Mustafa Al Bakri, Abdullah; Siew, Choo Chin; Nur Liza, Rahim; Nabiałek, Marcin (Polish Academy of Sciences, 2022)
With the rapid development of industry, abundant industrial waste has resulted in escalating environmental issue. Steel slag is the by-product of steel-making and can be used as cementitious materials in construction. However, the low activity of steel slag limits its utilization. Much investigation has been conducted on steel slag, while only a fraction of the investigation focuses on the effect of steel slag particle size on the properties of mortar. The aim of this study is to investigate the effect of steel slag particle size as cement replacement on properties of steel slag mortar activated by sodium sulphate (Na2SO4). In this study, two types of steel slag, classified as fine steel slag (FSS) with particle sizes of 0.075mm and coarse steel slag (CSS) with particle sizes of 0.150 mm, were used for making alkali activated steel slag (AASS) mortar. Flow table test, compressive strength test, flexural strength test and UPV test were carried out by designing and producing AASS mortar cubes of (50 × 50 × 50) mm at 0, 10%, 20% and 30% replacement ratio and at 0.85% addition of Na2SO4. The results show that the AASS mortar with FSS possess a relatively good strength in AASS mortar. AASS mortar with FSS which is relatively finer shows a higher compressive strength than CSS up to 38.0% with replacement.